STRUCTURING OF EDUCATIONAL MATERIAL IN PHYSICS AT THE TECHNICAL UNIVERSITY - Andrey V. Tyutyaev (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
One way to improve the efficiency of learning is the use of a deep logical structuring of educational information. In this paper, we propose a new method of structuring the teaching material in physics, while maintaining the traditional sequence of thematic modules: mechanical; thermodynamics and molecular physics (including elements of statistical physics); electricity and magnetism; waves, optics; quantum physics (including physics of the atom and elements of solid state physics); nuclear physics; physical picture of the world. As the most important concepts in physics arisen experiment are phenomenological and then physical knowledge can be represented on the one side, the experimental phenomenological laws describing various phenomena, on the other side, the pattern of these phenomena. The basis of the method of structuring the course of physics is to allocate the experimental laws and phenomenological models of varying complexity and generality, by which explained the mechanism of the phenomenon and process. In this case, models and hypotheses (classic-entry level, relativistic, quantum-higher level), by which explained the mechanisms of the phenomena that are of particular importance